A zero intermediate frequency RF transceiver with tunable operating frequency band. Issue 3 (12th January 2021) - Bai, Zhaojing; Wu, Yongle; Wang, Weimin; Wang, Xiaocheng
Abstract: A zero intermediate frequency (zero‐IF) radio frequency (RF) transceiver with tunable operating frequency band is proposed in this article, which consists of a transmitter (Tx), a receiver (Rx). Both the Tx and the Rx can achieve broadband operation. By tuning the carrier signal frequency ( f c ), the Tx and Rx can work in variable frequency band which is determined by f c . Therefore, a transceiver with tunable operating frequency band was realized. A prototype of the designed transceiver was designed, simulated, manufactured, and measured. In the end, a zero‐IF RF transceiver with tunable frequency band during 2.3 to 3.5 GHz was implemented. The gain range of the Tx is −35 to 28 dB. The gain range of the Rx is 28 to 78 dB. For 16‐QAM signal with a symbol rate of 15 MHz, the error vector magnitude of proposed Tx and Rx are less than 7.8% and 5.0%, respectively.